Size-controllable synthesis of hydroxyapatite nanorods via fluorine modulation: applications in dental adhesives for enhanced enamel remineralization - Linzhi Meng; Mengmeng Shu; Peng Mei; Yakun Liang; Lunguo Xia (BMC Oral Health)
Abstract Background There has been little application of fluorine-substituted hydroxyapatites (FHAs) in dental adhesives. Previous studies primarily focused on the effect of fluoride content on enamel remineralization, neglecting the role of FHA particle size. This study aimed to synthesize uniform FHA nanorods of varying sizes by adjusting the fluorine doping levels, and to investigate the synergistic effects of the fluorine content and nanorod size on enamel remineralization by incorporating the FHA nanorods into adhesives. Methods FHA nanorods with varying fluorine doping levels and sizes were synthesized based on a hydrothermal method. The characterization analyses of FHA nanorods were demonstrated by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM). The composite adhesives containing 10 wt% different FHA nanorods were characterized via scanning electron microscopy (SEM). The colloidal stability, light-curing poperties, and degree of conversion (DC %) were assessed. The shear bond strength (SBS) was determined and the failure mode analysis was reported. The release of Ca2+ and F− within 30 days was detected. The remineralization was evaluated via SEM, energy dispersive X-ray spectroscopy (EDS), XRD, and micro-hardness through in vitro and in vivo experiments. Statistical analyses were performed using the Shapiro-Wilk test, Levene test, one-way ANOVA, Tukey HSD method, Welch test, Tamhane test, Fisher’s exact test and Kruskal-Wallis test (α = 0.05). Results Uniform FHA nanorods of varying sizes were synthesized by adjusting the fluorine doping level (2 wt%, 6 wt%, and 10 wt%). The lengths of these FHA nanorods were 505.31 ± 104.43 nm, 111.27 ± 22.89 nm, and 66.21 ± 12.68 nm, respectively. The composite adhesives containing FHA nanorods showed good colloidal stability and appropriate light-curing properties. The SBS of composite adhesives decreased due to the incorporation of FHA nanorods, but the values still remained within the clinically required range. Three groups of the composite adhesives could release Ca2+ and F− continuously. The group of 10 wt% F-doped HA nanorods with shorter lengths exhibited more mineral deposition and absorption of Ca²⁺ onto the adhesive and enamel surfaces. Conclusions The strategy of adding the synthesized FHA nanorods into dental adhesives can be an effective approach to promote enamel remineralization, while maintaining adequate bond strength. The 10 wt% F-doped HA nanorods with shorter lengths exhibited superior remineralization.